Optimization of Plug-in HEV Power and Control Strategy Parameter based on the Particle Swam Optimization Algorithm - Yin Andong; Zhang Yu; Zhang Bingzhan; Zhao Han; Wang Ruofei (Jixie chuandong)
A newly developed plug-in hybrid electric vehicle is taken as research object and the vehicle simulation model is built by using CRUISE on the basis of completing the match of transmission parameters and control strategy design.An optimization model of plug-in HEV parameters is set up,applying optimization software Isight to integrate with CRUISE model.The constraints of the model are the designed power performance and the objective function is the fuel consumption and emission performance.The particle swarm optimization is applied to optimize the transmission system parameters and the control strategy parameter simultaneously.Compared the simulation results demonstrate that fuel consumption per hundred kilometer of PHEV is reduced by 12.5%and equivalent fuel consumption is reduced by 10.7% under UDDS driving cycle after optimization.